Effect of CeO2 nanoparticles on the microstructure and properties of the NiCo-CeO2 composite coatings. (February 2022) - You, Shuxin; Jiang, Chuanhai; Wang, Lianbo; Xing, Shilong; Zhan, Ke
Abstract: The NiCo-CeO2 composite coatings were electrodeposited on copper substrate in Watts' bath containing various CeO2 nanoparticle concentrations. The effect of CeO2 nanoparticles on the microstructure, surface residual stress and properties of NiCo-CeO2 composite coatings was studied. The nature and distribution of CeO2 nanoparticles in the NiCo-CeO2 composite coatings were analyzed by TEM. As the rise of CeO2 nanoparticle content in NiCo-CeO2 composite coatings, the microhardness of coating increased, which was because of the function of grain refinement and dispersion strengthening. Meanwhile, surface residual stress gradually increased as the rise of CeO2 nanoparticle content. Corrosion test result showed that increasing CeO2 nanoparticle content promoted the corrosion resistance of NiCo-CeO2 composite coatings. The NiCo-CeO2 composite coatings as the CeO2 nanoparticle concentration of 10 g/L had the highest corrosion resistance, which indicated that improvement of corrosion resistance needed a moderate amount of CeO2 nanoparticles. Particularly, the corrosion products were confirmed by XPS measurement, which demonstrated that CeO2 nanoparticles promoted the generation of corrosion products, resulting in the improved corrosion resistance. Highlights: The NiCo-CeO2 composite coatings were electrodeposited on copper substrate from Watts' bath. With the CeO2 content ascends in the NiCo-CeO2 composite coatings, (200) texture gradually disappears and the microhardness and residual stress increase monotonically. XPS analysis shows that CeO2 nanoparticles promote the production of corrosion products.